Board Effectiveness and Firm Profitability in Indonesian Consumer Goods Firms: The Role of Audit Quality and Marketing Intensity Financial Point of View - Komarudin, Mamay (Lembaga Teewan Journal Solutions, 2026)
A This study examines the association between board effectiveness, audit quality, marketing intensity, and profitability in consumer goods firms listed on the Indonesia Stock Exchange during 2018–2024. The study focuses on nine issuers observed over eight years, yielding a balanced panel of 72 firm-year observations. The main variables include Board Effectiveness Score (BES), return on equity (ROE), advertising intensity, market share, leverage (DER), and Big 4 audit quality. Methods: The analysis uses Seemingly Unrelated Regression (SUR) because the error terms across the two estimated equations are correlated. To assess robustness, the estimations are compared with Huber robust regression and bootstrap OLS confidence intervals. The results show that, within the estimated model, advertising intensity, market share, ROE, and leverage are positively associated with BES. In the profitability equation, BES and Big 4 audit quality are positively associated with ROE, while market share is negatively associated with ROE. Results: All seven formulated hypotheses were proven significant at 95% to 99% confidence intervals. These findings suggest that governance and profitability are related in ways that also reflect firms’ strategic and financial conditions. However, the results should be interpreted cautiously because the study relies on a small purposive sample, a composite governance measure, and an observational design that does not fully resolve endogeneity. The study therefore contributes sector-specific evidence rather than broad causal claims about corporate governance and firm profitability. Conclusion: The findings of this study confirm that corporate governance quality significantly correlates with profitability. These results reinforce the relevance of agency theory, signaling theory, and resource dependence theory in the context of emerging market capital markets.